2018
DOI: 10.1002/ejsp.2538
|View full text |Cite
|
Sign up to set email alerts
|

Right‐wing adherence and objective numeracy as predictors of minority group size perceptions and size threat reactions

Abstract: Racial, ethnic, religious, and sexual minority populations are growing rapidly in the West. We investigate predictors and consequences of threat responses to perceived minority group size, and perceptions of minority group size itself. Study 1 (N = 274) finds that right‐wing adherence predicts greater size threat, whereas lower numerical ability predicts larger perceived group size (confirmed in Studies 2–3). Study 2 (Sample 1, N = 124; Sample 2, N = 263) finds that the relation between right‐wing adherence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…More recently, researchers have turned their attention to the fluid nature of intergroup dynamics, in particular with regard to anticipated demographic changes and perceived outgroup size. For instance, across multiple studies, Earle and Hodson (2019) showed that those who perceived outgroup size to be threatening were more prejudiced toward the group in question (e.g., Muslims or LGBT people). Hence, simply perceiving that an outgroup is subjectively "too big" is associated with greater prejudice.…”
Section: Consequences Of Anticipated or Perceived Racial Shiftmentioning
confidence: 99%
“…More recently, researchers have turned their attention to the fluid nature of intergroup dynamics, in particular with regard to anticipated demographic changes and perceived outgroup size. For instance, across multiple studies, Earle and Hodson (2019) showed that those who perceived outgroup size to be threatening were more prejudiced toward the group in question (e.g., Muslims or LGBT people). Hence, simply perceiving that an outgroup is subjectively "too big" is associated with greater prejudice.…”
Section: Consequences Of Anticipated or Perceived Racial Shiftmentioning
confidence: 99%
“…In the Special Issue, Brown, Rucker and Richeson (2022) build on earlier work (e.g., Craig & Richeson, 2014), but introduce an important distinction between the perception of change in intergroup position and perceptions of threat associated with that change. Previous research on a related topic found value in differentiating between the perceived population size of an outgroup and the sense of threat associated with that size (see Earle & Hodson, 2019). In keeping with past research, Brown and colleagues exposed White participants to information about Whites becoming a minority in the near future (experimental) or control information (including, in some studies, that made race salient).…”
Section: Preview Of the Special Issuementioning
confidence: 99%
“…It is one thing to tolerate religious identity enactment, but another to accept that others are persuaded to express their identity in a similar way. Research has shown that the perception of minority group size is related to perceived threat (McLaren, 2003; Outten, Schmitt, Miller, & Garcia, 2011) and that ‘threat in numbers’ predicts negative attitudes towards minorities (Earle & Hodson, 2019). As such, trying to persuade others implies mobilizing fellow Muslims to engage in these practices, which majority group members may consider as threatening their identity and culture.…”
Section: Tolerance Of Enactment and Of Persuasionmentioning
confidence: 99%